The effect of cycling cadence on subsequent 10km running performance in well-trained triathletes - Tew, G. A. (Journal of Sports Science & Medicine, 2005)
The aim of this study was to examine the effects of different pedalling cadences on the performance of a subsequent 10km treadmill run. Eight male triathletes (age 38.9 ± 15.4 years, body mass 72.2 ± 5.2 kg, and stature 176 ± 6 cm; mean ± SD) completed a maximal cycling test, one isolated run (10km), and then three randomly ordered cycle-run sessions (65 minutes cycling + 10km run). During the cycling bout of the cycle-run sessions, subjects cycled at an intensity corresponding to 70% Pmax while maintaining one of three cadences, corresponding to preferred cadence (PC), PC+15% (fast cadence) and PC-15% (slow cadence). Slow, preferred and fast cadences were 71.8 ± 3.0, 84.5 ± 3.6, and 97.3 ± 4.3 rpm, respectively (mean ± SD). Physiological variables measured during the cycle-run and isolated run sessions were VO2, VE, RER, HR, RPE, and blood lactate. Biomechanical variables measured during the cycle-run and isolated run sessions were running velocity, stride length, stride frequency, and hip and knee angles at foot-strike and toe-off. Running performance times were also recorded. A significant effect of prior cycling exercise was found on 10km running time (p = 0.001) without any cadence effect (p = 0.801, ù2 = 0.006) (49:58 ± 8:20, 49:09 ± 8:26, 49:28 ± 8:09, and 44:45 ± 6:27 min·s-1 for the slow, preferred, fast, and isolated run conditions, respectively; mean ± SD). However, during the first 500 m of the run, running velocity was significantly higher after cycling at the preferred and fast cadences than after the slow cadence (p < 0.05). Furthermore, the slow cadence condition was associated with a significantly lower HR (p = 0.012) and VE (p = 0.026) during cycling than in the fast cadence condition. The results confirm the deterioration in running performance completed after the cycling event compared with the isolated run. However, no significant effect of cycling cadence on running performance was observed within the cadence ranges usually used by triathletes.